2016
DOI: 10.1007/s10899-016-9624-8
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Harm-Minimisation Tools Available for Electronic Gambling

Abstract: The increasing sophistication of gambling products afforded by electronic technologies facilitates increased accessibility to gambling, as well as encouraging rapid and continuous play. This poses several challenges from a responsible gambling perspective, in terms of facilitating player self-awareness and self-control. The same technological advancements in gambling that may facilitate a loss of control may also be used to provide responsible gambling tools and solutions to reduce gambling-related harm. Indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 74 publications
(132 reference statements)
1
77
0
Order By: Relevance
“…Reality checks have been posited as a mechanism for interrupting gambling or gaming to allow the player time to reflect to their actions (Harris and Griffiths 2017). This may take the form of session-time reminders or an in-built pause every 20 min during play.…”
Section: Responsible Gambling Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reality checks have been posited as a mechanism for interrupting gambling or gaming to allow the player time to reflect to their actions (Harris and Griffiths 2017). This may take the form of session-time reminders or an in-built pause every 20 min during play.…”
Section: Responsible Gambling Toolsmentioning
confidence: 99%
“…The relationship between electronic gambling and problem gambling is unclear and may be influenced by structural characteristics of specific games (Wood and Griffiths 2015). An argument has also been put forward that the same technological advancements utilised in online gambling may also be used to provide responsible gambling tools and solutions to reduce gambling-related harm (Harris and Griffiths 2017). Furthermore, it has been suggested that a lack of regulatory standards online leaves online gamblers vulnerable without adequate consumer protection, and this was highlighted by Gainsbury et al (2013) who found that around one-third of online gamblers have disputes with online gambling sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Player protection and harm minimization have become increasingly important in the gambling industry and have led to many gambling operators providing responsible gambling tools to their clientele (Griffiths 2012;Harris and Griffiths 2017). One of the most popular responsible gambling applications is the provision of pre-commitment limit-setting tools where players can pre-determine the amount of money and/or time they spend gambling within a specified time period (typically per day, per week, and/or per calendar month) (Wood and Griffiths 2010).…”
Section: Limit-setting Tools In Gambling Environmentsmentioning
confidence: 99%
“…However, given the high rate of players who did not accurately recall the content of a pop-up message that was observed in the current study, the efficacy of providing players with (nuanced) information in a pop-up message as a method for advancing informed decision making is brought into question. Although there is a large body of empirical evidence that limit-oriented pop-up messages facilitate limit adherence Auer & Griffiths, 2013;Harris & Griffiths, 2017;Kim et al, 2014;, it could be that the content of the message is irrelevant to its success. Specifically, players may simply infer that the presence of the pop-up means that their limit has been reached.…”
Section: Discussionmentioning
confidence: 99%